A Needs Analysis for the Development of Problem-Based Learning Student Worksheets Integrating Socio-Scientific Issues in the Topic of Reaction Rates to Enhance the Critical Thinking Skills of Senior High School - Mizatul Jannah; Fauzana Gazali; Daswarman Daswarman (Jurnal Riset Pendidikan Kimia (JRPK), 2026)
Instruction on reaction rates continues to face challenges in helping students grasp abstract concepts, link these concepts to real-world phenomena, and develop critical thinking skills. Furthermore, the Student Worksheets (LKM) currently used in schools do not optimally support contextual learning or problem-solving activities. Integrating Problem-Based Learning (PBL) with Socio-Scientific Issues (SSI) into these worksheets offers a relevant approach to introducing real-world problems as learning contexts that foster analysis, argumentation, and scientific decision-making. This study aimed to identify the requirements for developing Student Worksheets that incorporate a PBL model integrated with SSI for the topic of reaction rates. A descriptive method utilizing a survey approach was employed to assess development needs. The study participants consisted of 5 senior high school chemistry teachers and 71 senior high school chemistry students in West Sumatra. Data were collected through teacher interviews and student needs questionnaires using a Likert scale. The findings indicate that the majority of students still struggle to understand reaction rate concepts and relate them to everyday phenomena. Additionally, students require contextually designed worksheets to support their learning, and there was unanimous student support for the development of PBL-SSI integrated worksheets. Students also expressed a need for engaging, contextual teaching materials that facilitate problem-solving activities to hone critical thinking skills. These findings serve as the foundation for developing PBL-SSI integrated worksheets designed to connect reaction rate concepts with contextual issues while simultaneously fostering students' critical thinking skills.